2021
DOI: 10.24256/itj.v3i1.1744
|View full text |Cite
|
Sign up to set email alerts
|

Online Teaching Self-Efficacy – How English Teachers Feel During the Covid-19 Pandemic

Abstract: The transition from traditional face-to-face to online teaching during the Covid-19 pandemic happened so rapidly that most teachers started teaching without enough training, preparation, and knowledge of online teaching. In order to better understand this current teaching paradigm, the present research examined how English teachers perceive their own ability to teach online. It investigated English teachers’ self-efficacy to teach online by surveying 138 EFL university teachers in Japan. A survey with 29 Liker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Other findings that are salient to the current issue regarding the study are about the perspectives on the effectiveness of CLT through synchronous online learning. Thus, it has been found from the past studies by Lee and Ogawa (2021), where the finding manifested that there are pros and cons during the implementation of CLT through synchronous online learning. The teacher gave positive feedback towards the usage of technology during the lesson since they could learn new things and discover current features of the online platforms but it can be identified from the survey that teachers are least efficacious towards the classroom management during online learning.…”
Section: Discussionmentioning
confidence: 93%
“…Other findings that are salient to the current issue regarding the study are about the perspectives on the effectiveness of CLT through synchronous online learning. Thus, it has been found from the past studies by Lee and Ogawa (2021), where the finding manifested that there are pros and cons during the implementation of CLT through synchronous online learning. The teacher gave positive feedback towards the usage of technology during the lesson since they could learn new things and discover current features of the online platforms but it can be identified from the survey that teachers are least efficacious towards the classroom management during online learning.…”
Section: Discussionmentioning
confidence: 93%
“…In online teaching environments, teachers with ongoing support have a greater sense of efficacy when designing and delivering online courses (Richter and Idleman, 2017;Chung and Chen, 2018), and they experience less stress and burnout (Barni et al, 2019) and feel more satisfied with their teaching (Stickney et al, 2019). Recent research has also revealed that the enhancement of the teaching efficacy and satisfaction of EFL teachers in online teaching environments largely derives from administrative and peer support (Lee and Ogawa, 2021).…”
Section: Literature Teaching Supportmentioning
confidence: 99%
“…The topic of teachers' beliefs about and perceptions of their own teaching abilities, known as teaching efficacy, has attracted a great deal of attention from educational professionals and researchers (Tschannen-Moran and McMaster, 2009;Richter and Idleman, 2017). Teachers with a higher sense of efficacy tend to engage in innovative teaching to meet the unique needs of their students and to achieve satisfaction with their teaching (Lee and Ogawa, 2021). Although previous studies have emphasised the significance of teaching efficacy and its relations to teaching environments and performances at different educational levels, there still remains inconsistency in the relationships between these variables in different educational environments.…”
Section: Introductionmentioning
confidence: 99%
“…The self-efficacy is investigated to see whether there is a relationship with these variables or not. Variables selected by researchers for these groups of teachers include age (Özkara, 2019), teacher motivational strategies, teachers' general beliefs, student's motivation and achievement, classroom management, teaching practices, ( Al Rawahi et al, 2019;Alibakhshi et al, 2020;and Sabet et al, 2018), cultural context (Barabadi et al, 2018;Phan, 2016;Phan & Locke, 2016), various instructions, and professional development programs (Lailiyah & Cahyono, 2017;Ravandpour, 2019;Wyatt & Dikilitaş, 2016), job satisfaction ( Safari et al, 2020), burn-out (Fathi, & Saeedian, 2020;Roohani & Iravani, 2020), psychological wellbeing , teachers' empowerment (Azizifar, et al, 2020), self-regulation (Noughabi & Amirian, 2020) and online teaching Lee & Ogawa, 2021). The self-efficiency of teachers depends heavily on these variables since they help increase teachers' confidence in their capacity and competence to carry out tasks without giving up (Bandura, 1997).…”
Section: Theories and Data Collection Toolsmentioning
confidence: 99%